Optimization Telecommunications Infrastructure Projects for University Area - Supriyanto, Supriyanto; Ahyudanari, Ervina; Samopa, Febriliyan (Institut Teknologi Sepuluh Nopember, 2020)
In 2018-2019, utilization of data-based telecommunication was increased 82%. Signal measurement in Universitas Airlangga Surabaya is still low coverage because the distance between telecommunication towers and buildings. Surabaya City Government regulates the control of telecommunication towers including tower height, land, aesthetic, and tower sharing. One approach to solve this problem involves the use of concept Outdoor Distributed Antenna System (ODAS) or known as Base Transceiver Station Hotel (BTSH) which is support Microcell Pole (MCP), fiber-optic cable transmission, with configuration A Multiple-Carrier Multiple-Technology (MCMT). The tower provider company needs Optimal Hotel BTS design with measurement methods like Signal Strength, Signal Quality, and Point of Interest (POI). Planning a project schedule and project cost is using Critical Path Method (CPM) and Analytical Hierarchy Process (AHP) for further consideration regarding some criteria like revenue, cost, and technical. This analysis found that the most optimal calculation based on criteria weight is alternative project-1, by build a BTS Hotel in campus C, an 8 MCP tower, MCP fiber-optic cable with length Â± 2418 m, and connecting campus A, B, C with length Â± 8818 m, then project duration in 137 days with cost estimation IDR 7.8 billion.